2006
DOI: 10.1590/s0100-879x2006000600005
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Marchantia convoluta leaf extracts to human liver and lung cancer cells

Abstract: The cytotoxicity of three extracts (petroleum ether, ethyl acetate and n-butanol) from a plant used in folk medicine, Marchantia convoluta, to human non-small cell lung carcinoma (H1299) and liver carcinoma (HepG2) cell lines was tested. After 72-h incubation of lung and liver cancer cell cultures with varying concentrations of extracts (15 to 200 µg/mL), cytotoxicity was determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and reported in terms of cell viability. The extracts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…Cytotoxicity is expressed as the concentration of the substance (essential oil and terpenes) inhibiting cell growth by 50% (CD 50 ). Three replicate plates were used to determine the cytotoxicity of each sample (Stavri et al, 2005;Hou et al, 2006, Xiao et al, 2006.…”
Section: In Vitro Assay Cytotoxic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxicity is expressed as the concentration of the substance (essential oil and terpenes) inhibiting cell growth by 50% (CD 50 ). Three replicate plates were used to determine the cytotoxicity of each sample (Stavri et al, 2005;Hou et al, 2006, Xiao et al, 2006.…”
Section: In Vitro Assay Cytotoxic Activitymentioning
confidence: 99%
“…leaves was determined (Moura et al, 2006). Despite not being preponderant, the oil analyses showed that among its numerous constituents, there are some components described in literature as cytotoxic substances against tumoral cells, such as β-caryophyllene (5.9%), β-elemene (3.1%), δ -elemene (1.6%), α-humulene (2.3%) (Duh et al, 1999;Legault et al, 2003;Sibanda et al, 2004;Sylvestre et al, 2005;Stravi et al, 2005;Tatman and Mo, 2002;Wang et al, 2005;Sylvestre et al, 2006;Hou et al, 2006;Tao et al, 2006;Xiao et al, 2006. Some other components with no or low antitumoral activity were also found in this species, eg sphathulenol (3.8%), á-pinene (6.4%), linalool (0.5%), myrcene (0.6%) (Fullas et al, 1994;Tatman & Mo, 2002;Stavri et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A high dosage of flavonoids from M. convoluta (20 and 40 µg/mL) can significantly reduce the activity of ALT (Alanine aminotranferease) and AST (Alanine aminotranferease) in the serum of mice with acute hepatic injury caused by CCl 4 and increase the contents of TP (Total protein) and ALP (Alkaline phosphatase), as well as inhibit the auricle tympanites of mice caused by dimethylbenzene 1 . Flavonoids from M. convoluta strongly inhibited bacteria, anti-inflammation and diuresis in mice The ethyl acetate extract from M. convoluta strongly inhibited tumors in human liver and lung cancer cell lines 3,11 . Flavonoids from M. convoluta strongly inhibit Staphylococcus aureus 1,10 .…”
Section: Introductionmentioning
confidence: 98%
“…Esteves et al (2005) have determined recently the composition of the essential oil obtained from C. sylvestris leaves and verified that the major component is the bicyclogermacrene (40.9%), a component with low antitumoral potential. Nevertheless, a high percentage of this essential oil (around 17.5%) is constituted by two sesquiterpens, which cytotoxic activity is very potent and well characterized: β-caryophyllene (13.8%) and α-humulene (3.7%) (Duh et al, 1999;Tatman et al, 2002;Sibanda et al, 2004;Sylvestre et al, 2005;Sylvestre et al, 2006;Hou et al 2006;Xiao et al, 2006). This work describes the evaluation of the C. sylvestris essential oil cytotoxity against tumor cells (HeLa, A-549 and HT-29 cell lines).…”
Section: Introductionmentioning
confidence: 99%